Financing constraints, firm level adjustment of capital and aggregate implications - Ulf von Kalckreuth (Deutsche Bundesbank, 2008)
Following a positive shock, financing constraints will prolong or impede economic expansion that would have been optimal in an unconstrained environment. The study of dynamic adjustment therefore offers a direct way of verifying the presence of financing constraints and assessing their consequences for economic allocation. This paper compares the speed of adjustment of constrained and unconstrained firms using categorical information from survey data on the restrictions under which adjustment takes place. A set of moment conditions for the use in GMM estimation is developed, to cope with the problem of time varying speed of adjustment when the target level is partially unobserved. After estimating the micro-dynamics of capital demand, I show that the changing composition of the population makes for a time-varying sensitivity of the aggregate with respect to macroeconomic shocks. – – Wegen informationeller Friktionen, Unteilbarkeiten und Irreversibilitäten ist die Reaktion der aggregierten Faktornachfrage auf sektorale Schocks im Zeitablauf nicht unveränderlich. Sie wird vielmehr von der Verteilung der Firmen abhängen. Wenn viele Unternehmen sich in einem Zustand befinden, der eine rasche Reaktion erlaubt oder erzwingt, ist die Sensitivität hinsichtlich expansiver Schocks besonders groß. Aus diesem Grund sind direkte Informationen über die Position der Unternehmen von hohem Wert, da sie einen Aufschluss über die Sensitivität des Unternehmenssektors als Ganzem geben können. Diese Arbeit stellt heraus, dass Umfragedaten eine wichtige und zeitnahe Informationsquelle hinsichtlich der relevanten Beschränkungen für Individuen sein können. Es wird spezifisch die Bedeutung von Finanzierungsrestriktionen für die Anpassungsgeschwindigkeit auf der Mikroebene und deren Folgen für das Aggregat behandelt.
Keywords: D24; D21; C23; 330; Financing constraints; adjustment; dynamic panel data models; Verschuldungsrestriktion; |aInvestition; |aProduktionskapazität; |aKapazitätsauslastung; |aUnternehmensentwicklung; |aSchätzung; Deutschland